Phonology and language use - Bybee, Joan (Cambridge University Press, 2001)
Referencing new developments in cognitive and functional linguistics, phonetics, and connectionist modeling, this book investigates various ways in which a speaker/hearer's experience with language affects the representation of phonology. Rather than assuming phonological representations in terms of phonemes, Joan Bybee adopts an exemplar model, in which specific tokens of use are stored and categorized phonetically with reference to variables in the context. This model allows an account of phonetically gradual sound change which produces lexical variation, and provides an explanatory account of the fact that many reductive sound changes affect high frequency items first.